Hepatotoxicity of cyanotoxin microcystin-LR in human: Insights into mechanisms of action in the 3D culture model Hepoid-HepaRG - Chowdhury, Riju R; Rose, Sophie; Ezan, Frédéric; Sovadinová, Iva; Babica, Pavel; Langouët, Sophie (Environmental pollution (Barking, Essex, 2024)
Microcystin-LR (MC-LR) is a potent hepatotoxin produced by harmful cyanobacterial blooms (CyanoHABs). MC-LR targets highly differentiated hepatocytes expressing organic anion transporting polypeptides OATP1B1 and OATP1B3 that are responsible for hepatocellular uptake of the toxin. The present study utilized an advanced 3D in vitro human liver model Hepoid-HepaRG based on the cultivation of collagen-matrix embedded multicellular spheroids composed of highly differentiated and polarized hepatocyte-like cells. 14-d-old Hepoid-HepaRG cultures showed increased expression of OATP1B1/1B3 and sensitivity to MC-LR cytotoxicity at concentrations >10 nM (48 h exposure, EC20 = 26 nM). MC-LR induced neither caspase 3/7 activity nor expression of the endoplasmic reticulum stress marker gene BiP/GRP78, but increased release of pro-inflammatory cytokine IL-8, indicating a necrotic type of cell death. Subcytotoxic (10 nM) and cytotoxic (≥100 nM) MC-LR concentrations disrupted hepatocyte functions, such as xenobiotic metabolism phase-I enzyme activities (cytochrome P450 1A/1B) and albumin secretion, along with reduced expression of CYP1A2 and ALB genes. MC-LR also decreased expression of HNF4A gene, a critical regulator of hepatocyte differentiation and function. Genes encoding hepatobiliary membrane transporters (OATP1B1, BSEP, NTCP), hepatocyte gap junctional gene connexin 32 and the epithelial cell marker E-cadherin were also downregulated. Simultaneous upregulation of connexin 43 gene, primarily expressed by liver progenitor and non-parenchymal cells, indicated a disruption of tissue homeostasis. This was associated with a shift in the expression ratio of E-cadherin to N-cadherin towards the mesenchymal cell marker, a process linked to epithelial-mesenchymal transition (EMT) and hepatocarcinogenesis. The effects observed in the human liver cell in vitro model revealed mechanisms that can potentially contribute to the MC-LR-induced promotion and progression of hepatocellular carcinoma (HCC). Hepoid-HepaRG cultures provide a robust, accessible and versatile in vitro model, capable of sensitively detecting hepatotoxic effects at toxicologically relevant concentrations, allowing for assessing hepatotoxicity mechanisms, human health hazards and impacts of environmental hepatotoxins, such as MC-LR.
Keywords: Organic anion transporting polypeptides; Microcystin-LR; Chemical and Drug Induced Liver Injury; Humans; kadheriny; 3D human liver model Hepoid-HepaRG; mikrocystiny; lékové postižení jater; Microcystins; nádory jater; Cyanotoxins; Marine Toxins; hepatocelulární karcinom; Hepatocarcinogenesis; Carcinoma, Hepatocellular; mořské toxiny; Liver Neoplasms; lidé; Cadherins